Ex vivo fluorescence confocal microscopy: the first application for real‐time pathological examination of prostatic tissue. (17th April 2019) - Puliatti, Stefano; Bertoni, Laura; Pirola, Giacomo M.; Azzoni, Paola; Bevilacqua, Luigi; Eissa, Ahmed; Elsherbiny, Ahmed; Sighinolfi, Maria C.; Chester, Johanna; Kaleci, Shaniko; Rocco, Bernardo; Micali, Salvatore; et al.
Abstract : Objective: To report the first application of ex vivo fluorescence confocal microscopy (FCM) ‐ a novel optical technology that is capable of providing fast microscopic imaging of unfixed tissue specimens‐ in the urological field assessing its diagnostic accuracy for non neoplastic and cancerous prostate tissue (prostatic adenocarcinoma) compared to the 'gold standard' histopathological diagnoses. Patients and methods: In all, 89 specimens from 13 patients with clinically localised prostate cancer were enrolled into the study. All patients underwent robot‐assisted laparoscopic radical prostatectomy with fresh prostatic tissue biopsies taken at the end of each intervention using an 18‐G biopsy punch. Specimens were randomly assigned to the three collaborating pathologists for evaluation. Intra‐ and inter‐observer agreement was tested by the means of Cohen's κ. The diagnostic performance was evaluated on receiver operating characteristic curve analysis. Results: The overall diagnostic agreement between FCM and histopathological diagnoses was substantial with a 91% correct diagnosis (κ = 0.75) and an area under the curve of 0.884 (95% confidence interval 0.840–0.920), 83.33% sensitivity, and 93.53% specificity. Conclusion: FCM seems to be a promising tool for enhanced specimens' reporting performance, given its simple application and very rapid microscopic image generation (<5 min/specimen). This technique may potentially be used for intraoperative pathological specimens' analysis.